The TNAPP web-based algorithm improves thyroid nodule management in clinical practice: A retrospective validation study - Triggiani, Vincenzo; Lisco, Giuseppe; Renzulli, Giuseppina; Frasoldati, Andrea; Guglielmi, Rinaldo; Garber, Jeffrey; Papini, Enrico (Frontiers in Endocrinology, 2023)
The detection of thyroid nodules has been increasing over time, resulting in extensive use of fine-needle aspiration (FNA) and cytology. Tailored methods are required to improve the management of thyroid nodules, including web-based tools. To assess the performance of the Thyroid Nodule App (TNAPP), a novel web-based readily modifiable, interactive algorithmic tool, in improving the management of thyroid nodules. One hundred twelve consecutive patients with 188 thyroid nodules who had FNA from January to December 2016 and thyroid surgery were retrospectively evaluated. Neck ultrasound images were collected from registry and re-examined to extract data to run TNAPP. Each nodule was evaluated for ultrasonographic risk and suitability for FNA. The sensitivity, specificity, positive and negative predictive values, and overall accuracy of TNAPP were calculated and compared to the diagnostic performance of other two algorithms (AACE/ACE/AME and ACR TI-RADS). TNAPP performed better in terms of sensitivity (>80%) and negative predictive value (68%) with an overall accuracy of 50.5% which was similar to that found for the AACE/ACE/AME algorithm. The TNAPP displayed a slightly better performance compared to AACE/ACE/AME and ACR TI-RADS algorithms in discriminating unnecessary FNA for nodules with benign cytology (TNAPP 32% vs. AACE/ACE/AME 31% vs. ACR TI-RADS 29%). The TNAPP reduced the number of missed diagnoses of thyroid nodules with suspicious and highly suspicious cytology (TNAPP 18% vs. AACE/ACE/AME 26% vs. ACR TI-RADS 20.5%). Fourteen nodules that would not have been aspirated were malignant, 13 of which were microcarcinomas. The TNAPP algorithm is a reliable, easy to learn tool, that can be readily employed to improve the selection of thyroid nodules requiring cytological characterization. The rate of malignant nodules missed because of inaccurate characterization by TNAPP was low compared to the other two algorithms and almost all the cases were microcarcinomas. TNAPP’s use of size >20 mm as an independent determinant for considering or recommending FNA reduced its specificity. TNAPP performs well compared to AACE/ACE/AME and ACR-TIRADS. Additional retrospective and prospective studies are needed to confirm and guide the development of future iterations that incorporate different risk stratification systems and targets for diagnosing malignancy while reducing unnecessary FNA.